Introduction to engineering and scientific computing with Python - Clough, David E.; Chapra, Steven C. (Boca Raton : CRC Press, 2023)
"As more and more engineering departments, and companies choose to use Python, this book provides an essential introduction to this open-source, free to use language. Expressly designed to support first-year engineering students, this book covers engineering and scientific calculations, Python basics and structured programming. Based on extensive teaching experience, the text uses practical problem solving as a vehicle to teach Python as a programming language. By learning computing fundamentals, in an engaging and hands-on manner, it enables the reader to apply engineering and scientific methods to Python, focusing this general language to the needs of engineers and the problems they are required to solve on a daily basis. Rather than inundating students with complex terminology, the book is designed with a levelling approach in mind, enabling students at all levels to gain experience and understanding of Python. It covers topics such as structure programming, graphics, matrix operations, algebraic equations and differential equations. A comprehensive chapter on working with data brings the book to a close. This book is an essential guide to Python, which will be relevant to all engineers, particularly undergraduate students in their first year. It will also be of interest to professionals and graduate students looking to hone their programming skills, and to situate Python in an engineering and scientific context"--
Engineering and scientific calculations -- Computer-based calculations -- Python basics -- Structured programming with Python -- Graphics -- Matplotlib -- Array and matrix operations -- Solving single algebraic equations -- Solving sets of algebraic equations -- Solving differential equations -- Working with data.
OCLC-licensed vendor bibliographic record.
Keywords: Engineering mathematics -- Data processing; Science -- Mathematics -- Data processing; Python (Computer program language); COMPUTERS / General; MATHEMATICS / Arithmetic; TECHNOLOGY / Engineering / General